2002
DOI: 10.1046/j.1365-294x.2002.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary distributional stasis in the submediterranean mountain plant Anthyllis montana L. (Fabaceae) inferred from ITS sequences and amplified fragment length polymorphism markers

Abstract: Anthyllis montana is a submediterranean, herbaceous plant of the southern and central European mountains. The internal transcribed spacer (ITS) regions of nuclear ribosomal DNA were sequenced from multiple accessions of the species and several closely related taxa. In addition, amplified fragment length polymorphism (AFLP) was analysed from 71 individuals of A. montana collected in 20 localities, mainly in the Pyrenees, Alps, Italian Peninsula and Balkans. Our ITS phylogeny showed a sequential branching patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 50 publications
(58 reference statements)
14
159
2
Order By: Relevance
“…On the contrary, at least for diving beetles the Pyrenees and the Ebro valley seem to have been almost insurmountable geographical barriers during most of the Pleistocene, isolating Iberian populations from those in the rest of Europe long enough for them to speciate in allopatry. This will be in agreement with recent work on other taxa, for which during the Pleistocene glaciations Iberia (and other peninsulas in southern Europe) could have remained isolated rather than being a refuge from where to re-colonise northern areas during the interglacials (Bilton et al, 1998;Kropf et al, 2002;Michaux et al, 2003). For these taxa, northern refuges could be the source of most present-day central and north European populations (e.g.…”
Section: Divergence Area Range and Habitatsupporting
confidence: 90%
“…On the contrary, at least for diving beetles the Pyrenees and the Ebro valley seem to have been almost insurmountable geographical barriers during most of the Pleistocene, isolating Iberian populations from those in the rest of Europe long enough for them to speciate in allopatry. This will be in agreement with recent work on other taxa, for which during the Pleistocene glaciations Iberia (and other peninsulas in southern Europe) could have remained isolated rather than being a refuge from where to re-colonise northern areas during the interglacials (Bilton et al, 1998;Kropf et al, 2002;Michaux et al, 2003). For these taxa, northern refuges could be the source of most present-day central and north European populations (e.g.…”
Section: Divergence Area Range and Habitatsupporting
confidence: 90%
“…Our study on T. alpinum provides, in addition to the data obtained for Rumex scutatus (Lauga et al, 2005), Trollius europaeus (Després et al, 2002) and Anthyllis montana (Kropf et al, 2002), a better understanding of today flora repartition and genetic structuring in this Southern European mountain massif. Even though interesting, the studies on Borderea chouardii (Segarra-Moragues et al, 2005) and B. pyrenaica (Segarra-Moragues & Catalan, 2003) are not considered here since it concerned specific cases of rare plants with a narrow distribution range.…”
Section: Patterns Of Genetic Diversity In Alpine Plants In the Pyrsupporting
confidence: 55%
“…Even though interesting, the studies on Borderea chouardii (Segarra-Moragues et al, 2005) and B. pyrenaica (Segarra-Moragues & Catalan, 2003) are not considered here since it concerned specific cases of rare plants with a narrow distribution range. Hence, in spite of the reduced number of populations sampled in the Pyrenees (these studies were not focused on this massif), A. montana (Kropf et al, 2002) and T. europaeus (Després et al, 2002) exhibited, as in T. alpinum, an eastern/western biogeographic pattern along the Pyrenean massif. Interestingly, the Southern localities included in Kropf 's study indicated that the western Pyrenean population of A. montana showed similarity to western (Sierra de Cantabria) and southern (Sierra de Baza) Spanish populations whereas the eastern Pyrenean population was more divergent from them (Kropf et al, 2002) .…”
Section: Patterns Of Genetic Diversity In Alpine Plants In the Pyrmentioning
confidence: 99%
“…These data clearly show that Vermifrux abyssinica cannot be placed in Anthyllis. However, the type species of Dorycnopsis, D. gerardii, has not yet been included in molecular phylogenetic analyses of Loteae (e.g., Allan & Porter, 2000;Kropf & al., 2002;Allan & al., 2003;Degtjareva & al., 2003;Nanni & al., 2004). Therefore, we have decided to produce and analyse nrITS sequences of Dorycnopsis gerardii to resolve its taxonomic position.…”
Section: Introductionmentioning
confidence: 99%